Isolation of Genes Encoding Arthropod Odorant Binding Proteins (OBP), D7 from Salivary Gland Vectors of Malaria: Anopheles sundaicus - Nuryatmaja Gora Pawana; Kahar Muzakhar; Kartika Senjarini (Jurnal ILMU DASAR, 2015)
The isolation of Arthropod Odorant Binding, D7 protein, encoding genes from Anopheles sundaicus and An. maculatus mosquitos as the malaria vectors in Indonesia is necessary to recognize their characteristic. The isolated genes can be used to develop the Transmission Blocking Vaccine (TBV). This research aims to characterize the D7 protein encoding genes from An. sundaicus and An. maculatus through the synthesis of complementary DNA (cDNA) of D7 protein by using D7 protein primer that has been used for the other species of Anopheles. The mosquitos were taken from Dusun Parasputih, Bangsring, Wongsorejo, Banyuwangi, Jawa Timur. Isolation of the salivary gland was done by performing microdisection method and the isolation of the total RNA was done by performing High Pure RNA Isolation Kit (Roche-Germany). Synthesis of cDNA D7 encoding gene and its amplification were performed by using Maxime RT-PCR Premix Kit (iNtRon Biotechnology). The result of the total RNA and RT-PCR were run  in agarose gel and visualized under the UV transiluminator. Based on the visualization, we found that the salivary gland total RNA of female An. sundaicus was 500-750 base pair (bp). The RT-PCR visualization showed a band sized below 100 bp and it was concluded not to be the size of the D7 protein encoding gene. An incompatibility of D7 primer from An. gambiae with cDNA template from An. sundaicus was suspected to be the reason of the gene isolation failure.Keywords: gene isolation, D7 protein, salivary gland, Anopheles sundaicus